Action Research on Using Participatory Budgeting for Community Construction in Taiwan - Lai, Cheng-Neng; Hsieh, Cheng-Hsun; Hsieh, Chung-Heng; Chow, Genevieve (Advances in Social Sciences Research Journal, 2022)
In order to improve the participation from local residents during the decision-making about their public’s life, participatory budgeting is one of the most prevalent system of civic engagement recently. In this project, the site selected in Taiwan is a span space under expressway, is open to use as a park and physical fitness facility for the local residents. The action plan through explanatory presentation, empowerment and proposal workshop, project exhibition and voting, and preferred solution implementation. Using participatory budgeting as a tool of governance allows people to participate in the politics, and the government also wins the trust and obtain a higher satisfaction level from the public.